"Feeling at home” for people with dementia in care environments : the role of built environment factors. A critical literature review - Chen, Jing (2021)
ABSTRACT: This review summarises the challenges of applying evidence that built environment factors contribute to people with dementia feeling at home in long-term care institutions. Eighteen reviewed publications are classified into research-focused and practice-focused study. Research-focused studies from scientific epistemology focus on physical environment aspects that influence residents feeling at home in the care institution. Design-focused studies develop specific design strategies based on evidence from research-focused studies. However, there are limitations in transforming research evidence into design practice due to a mismatched knowledge foundation. Future research should consider standing on design epistemology to gain new insights which reflect built environment contributions to the sense of home for people with dementia living in care institutions by Research through Design approach.